2012
DOI: 10.4103/1735-3327.92925
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral Midazolam-Ketamine and Midazolam-Promethazine as sedative agents in pediatric dentistry

Abstract: Background:Investigation was designed to evaluate the behavioral changes in children receiving dental treatment while they have been administered combination of Midazolam/Ketamine or Midazolam/Promethazine.Materials and Methods:This was a randomized double blind clinical trial with cases being selected from those uncooperative children aged 2 to 6 years from those referred for treatment under general anesthesia. Anxiety score of all cases were recorded before any attempt using Frankel's anxiety scoring system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…In addition to the use of any sedative drugs, the use of local anesthesia is essential for most of the dental treatments. 8 , 11 , 24 , 27 Postoperative sleep phase was 0-1 hour for oral sedation with 2-3 hours for intranasal sedations at the recovery stage, with statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the use of any sedative drugs, the use of local anesthesia is essential for most of the dental treatments. 8 , 11 , 24 , 27 Postoperative sleep phase was 0-1 hour for oral sedation with 2-3 hours for intranasal sedations at the recovery stage, with statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of midazolam and ketamine as oral or nasal medication have been reported to boost the results. Vahid et al 24 compared oral midazolam (0/4 mg/kg)-ketamine (5 mg/kg) and midazolam (0/5 mg/kg)-promethazine (5 mg/mL) as sedative agents and concluded that ketamine/midazolam combination could sufficiently sedate children even in lower doses, unlike midazolam/promethazine combination used in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Golpayegani et al investigated that midazolam/ketamine cocktail had deeper sedative effects than midazolam/promethazine during the treatment ( 16 ). Pruitt et al observed that intramuscular injection of midazolam, ketamine, and glycopyrrolate cocktail has been accompanied with the suitable sedation level in medical diagnostic measures ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous sedation is the second most comfortable, effective, and the safest technique after inhalation sedation; however, the technique should be used only by trained personnel. [ 1 ] Sedative techniques do not involve intubation, contrasting general anesthesia and the recovery period is short. [ 2 ] There are basically two techniques available for intravenous sedation: Use of only one medication, which is usually benzodiazepine and a combination of several medicines.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] There are basically two techniques available for intravenous sedation: Use of only one medication, which is usually benzodiazepine and a combination of several medicines. [ 1 ] In sedation, it is of the utmost importance to achieve analgesia. Due to the limitations of the use of local anesthetic agents such as overdose and reaching the toxic levels of medications, proper analgesic agents should be used in combination with sedative agents.…”
Section: Introductionmentioning
confidence: 99%